2019
DOI: 10.1093/carcin/bgz069
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-valproic acid (MDC-1112) suppresses glioblastoma growth in preclinical models through the inhibition of STAT3 phosphorylation

Abstract: Abstract New therapeutic strategies against glioblastoma multiforme (GBM) are urgently needed. Signal transducer and activator of transcription 3 (STAT3), constitutively active in many GBM tumors, plays a major role in GBM tumor growth and represents a potential therapeutic target. We have documented previously that phospho-valproic acid (MDC-1112), which inhibits STAT3 activation, possesses strong anticancer properties in multiple cancer types. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In addition to their canonical roles in inflammation and immunity, STAT3 and STAT5 have been shown to localize to mitochondria. The mitochondrial localization of STAT3 is required for its ability to support malignant transformation in murine embryonic fibroblasts and breast cancer cells [43,44,45,46], and mito-STAT3 regulates mitochondrial metabolism and mitochondrial gene expression [45,47,48,49,50,51]. Several reports have suggested that STAT3 can be imported to mitochondria after phosphorylation on S727 [44,45] or upon acetylation [52,53].…”
Section: Mechanisms Of Transformation By Stat3/5 Proteins In Solidmentioning
confidence: 99%
“…In addition to their canonical roles in inflammation and immunity, STAT3 and STAT5 have been shown to localize to mitochondria. The mitochondrial localization of STAT3 is required for its ability to support malignant transformation in murine embryonic fibroblasts and breast cancer cells [43,44,45,46], and mito-STAT3 regulates mitochondrial metabolism and mitochondrial gene expression [45,47,48,49,50,51]. Several reports have suggested that STAT3 can be imported to mitochondria after phosphorylation on S727 [44,45] or upon acetylation [52,53].…”
Section: Mechanisms Of Transformation By Stat3/5 Proteins In Solidmentioning
confidence: 99%
“…In vivo, MDC-1112 reduced the growth of subcutaneous GBM xenografts in mice by up to 78.2% vs. controls. Moreover, MDC-1112 extended survival in an intracranial xenograft model [ 219 ].…”
Section: Aeds In Other Tumor Typesmentioning
confidence: 99%
“…In vivo, this new STAT3 inhibitor impaired glioma growth [179]. The use of MDC-1112, which was demonstrated to inhibit STAT3 phosphorylation at the serine 727, significantly inhibited the growth of GBM cell lines and their clonogenicity in vitro [180]. In vivo, it was associated with decreased tumor volume and increased mouse survival [180].…”
Section: Stat3 Pathwaymentioning
confidence: 99%
“…The use of MDC-1112, which was demonstrated to inhibit STAT3 phosphorylation at the serine 727, significantly inhibited the growth of GBM cell lines and their clonogenicity in vitro [180]. In vivo, it was associated with decreased tumor volume and increased mouse survival [180]. WP1066, which is now in a Phase I clinical trial recruiting patients with recurrent malignant gliomas (NCT01904123), showed promising preclinical results [181].…”
Section: Stat3 Pathwaymentioning
confidence: 99%